Single Dose Pharmacokinetics of α-Dihydroergocryptine in Patients with Moderate to Severe Renal Insufficiency - Mey, Christian de; Sułowicz, Władyslaw; Stompór, Tomasz; Ezan, Eric; Retzow, Angelika; Althause, Michael (Arzneimittelforschung, 2003)
Aim: This study was carried out to evaluate the pharmacokinetic profile of α-dihydroergocryptine (CAS 14271-05-7, DHEC, Almirid®) in plasma and urine in patients with moderately to severely impaired renal function (creatinine clearance < 30 ml · min−1 · 1.73 m−2), following administration of single oral doses.Methods: This was an open, nonrandomised trial. Seven patients with chronic renal disease and six healthy subjects received a single dose of 20 mg DHEC. Blood and urine samples were taken at specified intervals up to 72 h after dosing. Concentrations of unchanged DHEC were determined by radio-immunoassay (RIA) and concentrations of unchanged DHEC plus pooled metabolites by enzyme-immunoassay (EIA), respectively.Results: In patients with impaired renal function, the mean Cmax and AUC(0–ȡ) values for unchanged DHEC were 2.1 (95 % confidence interval CI: 0.99 to 4.42) and 1.85 (95 % CI: 0.72 to 4.77) times larger than in controls. The 24-h urinary excretion was only 0.3 (95 % CI: 0.12 to 0.71) times that in healthy subjects. Similar findings were recorded for total DHEC plus metabolites.Conclusions: As treatment with DHEC is in general uptitrated starting with doses as low as 5 mg DHEC, which are then increased while accounting for individual effects both in terms of efficacy and tolerability, the observed range of effects of impaired renal function on DHEC’s pharmacokinetics does not suggest the need to revise this policy, although lower end-doses are likely to be achieved.
Keywords: Almirid®; CAS 14271-05-7; α-Dihydroergocryptine, clinical pharmacokinetics; Dopamine agonist; Renal insufficiency